Ocular effects of retrobulbar block with different local anesthetics in healthy dogs - Honsho, Cristiane dos Santos; Franco, Leandro Guimaraes; Cerejo, Sofia de Amorim; Segato, Murici Belo; Ferreira, Marco Antonio; Bolzan, Aline Adriana; Nishimori Duque, Celina Tie; Laus, Jose Luiz [UNESP] (Univ Estadual Londrina, 2014)
The objective of this study was to evaluate the ocular effects, the feasibility and the quality of retrobulbar block using the inferior temporal technique with different local anesthetics applied with the Tuohy epidural needle in dogs. Eight dogs were included in the experiment and each one was studied four times, with interval of 15 days between the treatments: Lido -2% lidocaine, Ropi - 0.75% ropivacaine, Bupi - 0.5% racemic bupivacaine and Levo - 0.75% levobupivacaine. Except for the ropivacaine, all of the local anesthetics contained epinephrine at 1: 200.000. The blocks were performed in the right eyes immediately after anesthetic induction, and the left eyes were not blocked and were used as controls. The intraocular pressure, tear production and corneal sensitivity were evaluated before any procedure (T0), 30 min after premedication (TMPA), 30 min after anesthetic induction (T30), after recovery from anesthesia (TREC), every 60 min up to 360 min and 12 and 24 h after the block. The pupil diameter was evaluated at the same time points, excepted at T0. The maximum pupillary dilatation was observed in Lido group at T120 followed by Ropi at TREC, and Bupi and Levo at T30. All of the anesthetics maintained eye pressure within acceptable levels for normal dogs and significantly reduced tear production. Tear production returned earliest in group Lido, followed by Bupi, Ropi and Levo. The corneal sensitivity returned earliest in group Lido, followed by Ropi, Bupi and Levo. The retrobulbar block using the temporal inferior technique proved to be feasible and safe, although lubrication of the ocular surface is suggested.

O objetivo deste estudo foi avaliar os efeitos oculares, a exequibilidade e qualidade do bloqueio retrobulbar pela técnica inferior temporal, em cães, com diferentes anestésicos locais empregando-se agulha epidural de Tuohy. Oito cães foram incluídos no experimento e cada um foi estudado quatro vezes, com intervalo de 15 dias entre os tratamentos: Lido - lidocaína a 2%; Ropi - ropivacaína a 0,5%, Bupi - bupivacaína racêmica a 0,5% e Levo - levobupivacaína a 0,75%. Com exceção da ropivacaína, todos os anestésicos continham epinefrina 1:200.000. Os bloqueios foram realizados nos olhos direitos dos animais imediatamente após a indução anestésica, e os olhos esquerdos, não bloqueados, foram utilizados como controle. Avaliou-se a pressão intraocular, a produção lacrimal e a sensibilidade corneal antes de qualquer procedimento (T0), 30 min após a medicação pré-anestésica (TMPA), 30 min após a indução anestésica (T30), após a recuperação da anestesia (TREC), a cada 60 min até 360 min e 12 e 24 h após o bloqueio. O diâmetro pupilar foi avaliado nos mesmos momentos, exceto no T0. A máxima dilatação pupilar foi observada no grupo Lido seguida pelos grupos Ropi, Bupi e Levo. Todos os anestésicos mantiveram a pressão ocular dentro dos níveis normais para cães e reduziram significativamente a produção lacrimal. A produção lacrimal retornou ao normal primeiramente no grupo Lido, seguida pelos grupos Bupi, Ropi e Levo. O retorno da sensibilidade corneal ocorreu primeiramente no grupo Lido, seguido pelos grupos Ropi, Bupi e Levo. O bloqueio retrobulbar pela técnica inferior temporal demonstrou ser exequível e seguro, embora o uso de lubrificantes oculares seja sugerido
Repercussões oculares do bloqueio retrobulbar com diferentes anestésicos locais em cães normais
Keywords: Bupivacaine; Dogs; lEvobupivacaine; Lidocaine; Ropivacaine; Bupivacaína; Cães; Levobupivacaína; Lidocaína; Ropivacaína